Transcriptional Activation, Deactivation and Rebound Patterns in Cortex, Hippocampus and Amygdala in Response to Ketamine Infusion in Rats - Kim, Jenny J.; Sapio, Matthew R.; Vazquez, Fernando A.; Maric, Dragan; Loydpierson, Amelia J.; Ma, Wenting; Zarate, Carlos A.; Iadarola, Michael J.; Mannes, Andrew J. (Frontiers in Molecular Neuroscience, 2022)
Ketamine, an N-methyl-D-aspartate (NMDA)-receptor antagonist, is a recently revitalized treatment for pain and depression, yet its actions at the molecular level remain incompletely defined. In this molecular-pharmacological investigation in the rat, we used short- and longer-term infusions of high dose ketamine to stimulate neuronal transcription processes. We hypothesized that a progressively stronger modulation of neuronal gene networks would occur over time in cortical and limbic pathways. A continuous intravenous administration paradigm for ketamine was developed in rat consisting of short (1 hr) and long duration (10 hr, and 10 hr + 24 hr recovery) infusions of anesthetic concentrations to activate or inhibit gene transcription in a pharmacokinetically-controlled fashion. Transcription was measured by RNA-Seq in three brain regions: frontal cortex, hippocampus, and amygdala. Cellular level gene localization was performed with multiplex fluorescent in situ hybridization. Induction of a shared transcriptional regulatory network occurred within 1 hr in all three brain regions consisting of (a) genes involved in stimulus-transcription factor coupling that are induced during altered synaptic activity (immediate early genes, IEGs, such as c-Fos, 9-12 significant genes per brain region, p < 0.01 per gene) and (b) the Nrf2 oxidative stress-antioxidant response pathway downstream from glutamate signaling (Nuclear Factor Erythroid-Derived 2-Like 2) containing 12-25 increasing genes (p < 0.01) per brain region. By 10 hrs of infusion, the acute results were further reinforced and consisted of more and stronger gene alterations reflecting a sustained and accentuated ketamine modulation of regional excitation and plasticity. At the cellular level, in situ hybridization localized up-regulation of the plasticity-associated gene Bdnf, and the transcription factors Nr4a1 and Fos, in cortical layers III and V. After 24 hr recovery, we observed overshoot of transcriptional processes rather than a smooth return to homeostasis suggesting an oscillation of plasticity occurs during the transition to a new phase of neuronal regulation. These data elucidate critical molecular regulatory actions during and downstream of ketamine administration that may contribute to the unique drug actions of this anesthetic agent. These molecular investigations point to pathways linked to therapeutically useful attributes of ketamine.